A Mindfulness-Based Lifestyle Intervention for Obese, Inactive Endometrial Cancer Survivors: A Feasibility Study. (September 2017) - Lucas, Alexander R.; Focht, Brian C.; Cohn, David E.; Buckworth, Janet; Klatt, Maryanna D.
Background: Mindfulness-based interventions (MBIs) to address self-regulation and lifestyle behaviors (diet, physical activity) may benefit endometrial cancer survivors (ECS), who are at increased risk for morbidity and mortality associated with obesity. However, the acceptability of mindfulness training and whether it can augment behavior change in ECS is unknown. We aimed to examine; 1) the feasibility of the Mindfulness in Motion + Diet (MIM+D) intervention and 2) the preliminary efficacy of MIM+D for improving mindfulness, diet, PA and health-related quality of life (HRQL). Methods: ECS (Mage=62.4, ±5yrs from diagnosis) completed assessments at baseline, 8 and 14 weeks. Feasibility was determined by intervention completion surveys, attendance and adherence data. We used repeated measures ANOVA's (SPSS 22.0) and effect size estimates (Cohen's d) to examine changes in mindfulness, diet, PA, and HRQL over time. Results: Thirteen ECS (76%) completed the MIM+D program and attendance (≥6/8 sessions) was 90%. Women reported favorably on the overall quality (mean of 4.75/5) and benefits of the MIM+D program; however, would have preferred receiving MIM+D closer to diagnosis. Intention to treat analyses found MIM+D did not significantly improve any outcomes. However, an intervention completers analysis showed significant change in mindfulness (p=.0039) and small to moderate estimates for change in fruits and vegetable intake (d=.23), MVPA (d=.45), RAND SF-36: MCS (d=.46), and sleep quality (d=.68). Conclusions: Integrating mindfulness training into behavioral interventions is feasible and ECS that adhere to these lifestyle programs may benefit. However, to future research should examine the-long term effects of mindfulness-based behavioral lifestyle interventions.